Policy publicness: argumentative strategies of Dilma Rousseff against impeachment - Pozobon, Rejane de Oliveira (2017)
This study aims, through a brief literature review, to approach the concept of publicness (CASAQUI, 2004, 2005, 2009, 2011, 2014; ROMEYER, 2015) used in the organizational and health fields to the political field. To exemplify this approach, we will analyze, through the theory of argumentation (BRETON, 2003), the pronouncements of president Dilma Rousseff before and after the opening of the impeachment voting proceedings in the House of Representatives, which were broadcasted on the Facebook social online network. We realize that, to adapt to media logics, the politician makes use of argumentative strategies and incorporate the art of representation and staging, acquiring features that were not present in the previous times.